Method for preparing high-compaction lithium iron phosphate material and application
By preparing high-pressure lithium iron phosphate material, the problem of low compaction density of the positive electrode material of lithium iron phosphate battery in the prior art is solved, and the battery energy density and electrochemical performance are improved.
Patent Information
- Application Number
- CN202411927912.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-25
- Publication Date
- 2025-03-28
AI Technical Summary
The compaction density of the existing lithium iron phosphate battery positive electrode material is low, which limits the energy density of the battery.
Two particles of different particle sizes are prepared by ball milling, sand milling, spray drying and sintering, and mixed and crushed in a specific proportion to prepare high-pressure lithium iron phosphate material.
The compaction density of lithium iron phosphate material is improved, the energy density of the battery is improved, and the electrochemical performance is improved.
Smart Images

Figure CN119706781A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of methods for preparing positive electrode materials for lithium-ion batteries, and in particular to a method for preparing high-density lithium iron phosphate materials and applications thereof. Background Art
[0002] The increasingly severe energy crisis is one of the major challenges facing mankind in the 21st century. In order to meet the growing energy needs of mankind, it is crucial to develop new energy sources that are environmentally friendly and sustainable. Lithium-ion batteries have the advantages of high operating voltage and high energy density, and are the most promising secondary batteries. Lithium iron phosphate, as the positive electrode material of lithium-ion batteries, has the advantages of high capacity, long cycle life, high thermal stability, environmental friendliness, and low cost. The compaction density has a great influence on the performance of lithium-ion batteries, and is closely related to the specific capacity, efficiency, internal resistance, and battery cycle performance of the electrode. Generally speaking, the greater the compaction density, the higher the energy density of the battery can be, so the compaction density is also regarded as one of the reference indicators of the material energy density. Under certain process conditions, the greater the compaction density, the higher the energy density of the battery. At present, the compaction density of lithium iron phosphate on the market is mostly 2.2-2.4g / cm 3 , the low compaction density restricts the energy density of the battery. Summary of the invention
[0003] In view of the above, the present invention aims to solve at least one of the technical problems existing in the prior art. To this end, the present invention proposes a method for preparing a high-density lithium iron phosphate material and its application. The method prepares two kinds of particles by ball milling, sand milling, spraying, sintering and crushing an iron source, a lithium source and a phosphorus source twice, and then mixes and crushes the two kinds of particles in different proportions, and then mixes them to obtain a high-density lithium iron phosphate material.
[0004] To this end, an embodiment of the present invention provides a method for preparing a high-density lithium iron phosphate material, the method comprising: step S1: mixing an iron source with a lithium source and a phosphorus source in a certain proportion, adding a certain amount of a carbon source and an additive, ball milling, sand milling, spray drying, sintering and crushing at a certain temperature to obtain a particle A; step S2: mixing an iron source with a lithium source and a phosphorus source in a certain proportion, adding a certain amount of a carbon source and an additive, ball milling, sand milling, spray drying, and sintering at a certain temperature to obtain a particle B; step S3: adding a carbon source, a lithium source and a phosphorus source to the particle A, ball milling, spray drying, and sintering to obtain a particle C; step S4: adding a carbon source, a lithium source, an iron source and a dopant to the particle B, ball milling, sand milling, spray drying, and sintering to obtain a particle D; step S5: uniformly mixing the particles C and D in a certain proportion, and then crushing and mixing to obtain a high-density lithium iron phosphate material.
[0005] In some embodiments, in step S1, the iron source is one or more of ferric phosphate, ferrous oxalate, iron oxide, hydroxyferric phosphate, iron powder, and ferric nitrate; the lithium source is one or more of lithium carbonate, lithium phosphate, lithium hydroxide, lithium dihydrogen phosphate, lithium monohydrogen phosphate, lithium acetate, and lithium nitrate; the phosphorus source is one or more of phosphoric acid, lithium dihydrogen phosphate, ammonium dihydrogen phosphate, diammonium hydrogen phosphate, and ferric phosphate; the lithium source, iron source, and phosphorus source are added in a molar ratio of Li:Fe:P=[1.03-1.04]:1:[1.03-1.04].
[0006] In some embodiments, in step S1, the carbon source is one or more of sucrose, glucose, citric acid, starch, and polyethylene glycol; the amount of the carbon source added is based on the carbon content in the particle A being between 0.01% and 0.20%; the additive is selected from one or more of titanium dioxide, ammonium metavanadate, and niobium pentoxide, and the doping amount is controlled between 300 and 3000 ppm.
[0007] In some embodiments, in step S1, the sanding particle size is controlled to be between 0.50-0.90 μm; the sintering temperature is 700-800° C., and the sintering time is 5-15 h; and the particle size of particle A is between 3.0-10.0 μm.
[0008] In some embodiments, in step S2, the iron source is one or more of ferric phosphate, ferrous oxalate, iron oxide, hydroxyferric phosphate, iron powder, and ferric nitrate; the lithium source is one or more of lithium carbonate, lithium phosphate, lithium hydroxide, lithium dihydrogen phosphate, lithium monohydrogen phosphate, lithium acetate, and lithium nitrate; the phosphorus source is one or more of phosphoric acid, lithium dihydrogen phosphate, ammonium dihydrogen phosphate, diammonium hydrogen phosphate, and ferric phosphate; the lithium source, iron source, and phosphorus source are added in a molar ratio of Li:Fe:P=[1.03-1.04]:1:[1.03-1.04].
[0009] In some embodiments, in step S2, the carbon source can be one or more of sucrose, glucose, citric acid, starch, and polyethylene glycol; the amount of the carbon source added is based on the carbon content in the particle B being between 0.05% and 0.30%; the additive is selected from one or more of titanium dioxide, ammonium metavanadate, and niobium pentoxide, and the doping amount is controlled between 300 and 3000 ppm.
[0010] In some embodiments, in step S2, the sanding particle size is controlled between 0.40-0.80 μm; the sintering temperature is 450-650° C., and the sintering time is 5-15 h; and the particle size of particle B is between 2.0-5.0 μm.
[0011] In some embodiments, in step S3, the amount of carbon source added is based on the carbon content in the particle C being between 1.1% and 1.4%; the carbon source is one or more of sucrose, glucose, citric acid, starch, and polyethylene glycol; the lithium source is one or more of lithium carbonate, lithium phosphate, and lithium hydroxide; the phosphorus source is one or more of phosphoric acid, ammonium dihydrogen phosphate, diammonium hydrogen phosphate, and lithium dihydrogen phosphate; the ball milling particle size is between 0.80 and 1.50 μm; the sintering temperature is 750-850°C, and the sintering time is 5-10 hours.
[0012] In some embodiments, in step S4, the amount of carbon source added is based on the carbon content in the particle D being between 1.2% and 1.6%; the carbon source is one or more of amino acid titanium, titanium oxalate, and titanium citrate; the lithium source is one or more of lithium carbonate, lithium phosphate, and lithium hydroxide; the iron source is one or more of iron oxide, ferrous oxalate, ferric phosphate, and ferric citrate; the dopant is one or more of amino acid titanium, titanium oxalate, and titanium citrate; the sanding particle size is between 0.20 and 0.50 μm; the sintering temperature is 600-750°C, and the sintering time is 5-10h.
[0013] In some embodiments, in step S5, the amount of particle C and particle D added is in accordance with the mass ratio of particle C: particle D = [8:2] - [2:8], and the mixing time is 0.5h-3h; the crushing particle size satisfies: D10>0.30μm, D50=0.7-1.50μm, D90<8μm, D100<15μm, and after crushing, secondary mixing is performed for 0.5-3h to obtain high-density lithium iron phosphate material.
[0014] The method for preparing high-density lithium iron phosphate material provided in an embodiment of the present invention comprises mixing an iron source, a lithium source, a phosphorus source, a carbon source and an additive twice, respectively ball milling and sand milling, spray drying and sintering to obtain particles of two different particle sizes, and then mixing the two particles in a certain proportion, crushing and mixing again to prepare high-density lithium iron phosphate material. BRIEF DESCRIPTION OF THE DRAWINGS
[0015] Figure 1 A flow chart of a method for preparing a high-density lithium iron phosphate material provided by an embodiment of the present invention;
[0016] Figure 2 This is a SEM spectrum of the high-density lithium iron phosphate material prepared in Example 1 of the present invention;
[0017] Figure 3 is the XRD spectrum of the high-density lithium iron phosphate material prepared in Example 1 of the present invention;
[0018] Figure 4The charge and discharge curves (0.1C and 1C) of the button-type half-cell assembled with the high-density lithium iron phosphate material prepared in Example 1 of the present invention. DETAILED DESCRIPTION
[0019] Embodiments of the present invention are described in detail below, examples of which are shown in the accompanying drawings, wherein the same or similar reference numerals throughout represent the same or similar elements or elements having the same or similar functions. The embodiments described below with reference to the accompanying drawings are exemplary and are intended to be used to explain the present invention, and should not be construed as limiting the present invention.
[0020] The disclosure below provides many different embodiments or examples to realize different structures of the present invention. In order to simplify the disclosure of the present invention, the parts and settings of specific examples are described below. Of course, they are only examples, and the purpose is not to limit the present invention. In addition, the present invention provides various specific processes and examples of materials, but those of ordinary skill in the art can appreciate the reusability of other processes and / or the use of other materials.
[0021] The embodiment of the present invention provides a method for preparing a high-density lithium iron phosphate material. It should be noted that the high-density lithium iron phosphate material in the present invention refers to a material with a compaction density greater than 2.60 g / cm 3 Specifically, Figure 1 As shown, the method includes:
[0022] Step S1: mixing an iron source with a lithium source and a phosphorus source in a certain ratio, adding a certain amount of a carbon source and additives, ball milling, sand milling, spray drying, and then sintering and crushing at a certain temperature to obtain particles A;
[0023] Wherein, the iron source is one or more of ferric phosphate, ferrous oxalate, iron oxide, hydroxyferric phosphate, iron powder, and ferric nitrate; the lithium source is one or more of lithium carbonate, lithium phosphate, lithium hydroxide, lithium dihydrogen phosphate, lithium monohydrogen phosphate, lithium acetate, and lithium nitrate; the phosphorus source is one or more of phosphoric acid, lithium dihydrogen phosphate, ammonium dihydrogen phosphate, diammonium hydrogen phosphate, and ferric phosphate; the lithium source, iron source, and phosphorus source are added in a molar ratio of Li:Fe:P=[1.03-1.04]:1:[1.03-1.04].
[0024] In an embodiment of the present invention, the carbon source is one or more of sucrose, glucose, citric acid, starch, and polyethylene glycol; the amount of the carbon source added is based on the carbon content in the particle A being between 0.01% and 0.20%; the additive is selected from one or more of titanium dioxide, ammonium metavanadate, and niobium pentoxide, and the doping amount is controlled between 300 and 3000 ppm.
[0025] The sand grinding particle size is controlled between 0.50-0.90 μm; in the spray drying, the air inlet temperature is 200-220°C, the air outlet temperature is 80-110°C, the blast frequency is 80 Hz, and the final spray particle size is controlled between D50=20-40 μm; the sintering temperature is 700-800°C, and the sintering time is 5-15h; the particle size of the particle A is between 3.0-10.0 μm.
[0026] Step S2: mixing an iron source with a lithium source and a phosphorus source in a certain ratio, adding a certain amount of a carbon source and additives, ball milling, sand milling, spray drying, and then sintering at a certain temperature to obtain particles B;
[0027] Wherein, the iron source is one or more of ferric phosphate, ferrous oxalate, iron oxide, hydroxyferric phosphate, iron powder, and ferric nitrate; the lithium source is one or more of lithium carbonate, lithium phosphate, lithium hydroxide, lithium dihydrogen phosphate, lithium monohydrogen phosphate, lithium acetate, and lithium nitrate; the phosphorus source is one or more of phosphoric acid, lithium dihydrogen phosphate, ammonium dihydrogen phosphate, diammonium hydrogen phosphate, and ferric phosphate; the lithium source, iron source, and phosphorus source are added in a molar ratio of Li:Fe:P=[1.03-1.04]:1:[1.03-1.04].
[0028] In an embodiment of the present invention, the carbon source can be one or more of sucrose, glucose, citric acid, starch, and polyethylene glycol; the amount of the carbon source added is based on the carbon content in the particle B being between 0.05% and 0.30%; the additive is selected from one or more of titanium dioxide, ammonium metavanadate, and niobium pentoxide, and the doping amount is controlled between 300 and 3000 ppm.
[0029] The sand grinding particle size is controlled between 0.40-0.80 μm; in spray drying, the air inlet temperature can be 200-220°C, the air outlet temperature can be 80-110°C, the blast frequency can be 80 Hz, and the final spray particle size is controlled between D50=20-40 μm; the sintering temperature is 450-650°C, and the sintering time is 5-15h; the particle size of the particle B is between 2.0-5.0 μm.
[0030] Step S3: adding a carbon source, a lithium source and a phosphorus source to the particles A, then ball milling, spray drying, and sintering to obtain particles C;
[0031] The amount of carbon source added is based on the carbon content of the particles C being between 1.1% and 1.4%; the carbon source is one or more of sucrose, glucose, citric acid, starch, and polyethylene glycol; the lithium source is one or more of lithium carbonate, lithium phosphate, and lithium hydroxide; the phosphorus source is one or more of phosphoric acid, ammonium dihydrogen phosphate, diammonium hydrogen phosphate, and lithium dihydrogen phosphate; the ball milling particle size is controlled between 0.80 and 1.50 μm; in spray drying, the inlet air temperature is 200-220°C, the outlet air temperature is 80-110°C, the blast frequency is 80 Hz, and the final spray particle size is controlled between D50=20-40 μm; the sintering temperature is 750-850°C, and the sintering time is 5-10h.
[0032] Step S4: adding a carbon source, a lithium source, an iron source, and a dopant to the particle B, and then ball milling, sand milling, spray drying, and sintering to obtain a particle D;
[0033] Among them, the amount of carbon source added is based on the carbon content in the particles D being between 1.2% and 1.6%; the carbon source is one or more of amino acid titanium, titanium oxalate, and titanium citrate; the lithium source is one or more of lithium carbonate, lithium phosphate, and lithium hydroxide; the iron source is one or more of iron oxide, ferrous oxalate, ferric phosphate, and ferric citrate; the dopant is one or more of amino acid titanium, titanium oxalate, and titanium citrate; the sand grinding particle size is between 0.20 and 0.50 μm, and in spray drying, the inlet air temperature is 200-220°C, the outlet air temperature is 80-110°C, the blast frequency is 80 Hz, and the final spray particle size is controlled between D50=20-40 μm; the sintering temperature is 600-750°C, and the sintering time is 5-10h.
[0034] Step S5: uniformly mix the particles C and D in a certain proportion, and then crush and mix them to obtain high-density lithium iron phosphate material.
[0035] The amount of particles C and D added is in a mass ratio of particles C: particles D = [8:2] - [2:8], and the mixing time is 0.5h-3h; during the crushing process, the air pressure is controlled between 0.2-0.4Mpa, the grading frequency is 80-200Hz, and the crushing particle size satisfies: D10>0.30μm, D50=0.7-1.50μm, D90<8μm, D100<15μm, and after crushing, secondary mixing is performed for 0.5-3h to obtain high-density lithium iron phosphate material.
[0036] The method for preparing a high-density lithium iron phosphate material provided in an embodiment of the present invention comprises mixing an iron source, a lithium source, a phosphorus source, a carbon source and an additive twice, and then ball milling and sand milling, spray drying and sintering to obtain particles of two different particle sizes. The two particles are then mixed in a certain proportion, crushed and mixed again to prepare a high-density lithium iron phosphate material.
[0037] The preparation method provided by the present invention prepares large and small particles through a two-step method, avoiding the limitations of particle grading and the problem of poor consistency in the traditional process route. Ultra-small particles are prepared by a low-temperature solid-phase method, combined with secondary grinding and sintering, and the size and proportion of small particles are controllable and have good dispersibility, achieving a perfect match with other particles. Among them, the first sintering adopts a low-temperature and short-time process to prepare ultra-small particles and reduce manufacturing costs; the secondary sintering adopts high-temperature treatment, which can not only improve the integrity of the coating, but also repair the crystals, and generate primary particles of different sizes at this stage, thereby improving the compaction density and electrochemical properties of the lithium iron phosphate material.
[0038] The specific process and effect of the method for preparing high-density lithium iron phosphate material of the present invention are further described in detail below in combination with some specific embodiments, but are not limited to the protection scope of the present invention.
[0039] Example 1
[0040] This embodiment provides a method for preparing a high-density lithium iron phosphate material, comprising the following steps:
[0041] Step S1: mixing hydroxyferric phosphate with lithium phosphate and phosphoric acid in a molar ratio of Li:Fe:P=1.03:1:1.03, and adding a carbon source mixture consisting of sucrose and polyethylene glycol so that the carbon content in particle A is 0.05% and titanium dioxide with a doping amount of 1000ppm to form a mixture; sand-grinding the above mixture, controlling the sand-grinding particle size to 0.80μm, to obtain a nano-sized sand-grinding slurry; spray-drying the nano-sized sand-grinding slurry, controlling the inlet air temperature to 220°C, the outlet air temperature to 100°C, and the blast frequency to 80Hz, to obtain a spray material with a spray particle size of D50=20-40μm; placing the above spray material in a box furnace and sintering it in a nitrogen atmosphere, with a heating rate of 3°C / min, a sintering temperature of 780°C, and a sintering time of 10h, and then cooling it naturally to obtain a sintered material, and crushing the sintered material by a mechanical crusher to control the particle A with D50=6-10μm;
[0042] Step S2: iron phosphate and lithium carbonate are mixed in a molar ratio of Li:Fe:P=1.04:1:1.03, and a carbon source mixture consisting of sucrose and polyethylene glycol is added to make the carbon content in particle B 0.15% and titanium dioxide with a doping amount of 2500ppm to form a mixture; the mixture is sand-milled to control the sand-milling particle size to 0.55μm to obtain a nano-sized sand-milling slurry; the nano-sized sand-milling slurry is spray-dried to control the inlet air temperature to 220°C, the outlet air temperature to 100°C, and the blast frequency to 80Hz to obtain a spray material with a spray particle size D50=20-40μm; the spray material is placed in a box furnace and sintered in a nitrogen atmosphere at a heating rate of 3°C / min, a sintering temperature of 500°C, and a sintering time of 8h, and then cooled naturally to obtain particles B;
[0043] Step S3: Particle A and a carbon source consisting of sucrose and polyethylene glycol that makes the carbon content of particle C 1.2% are mixed to form a mixture; lithium carbonate accounting for 0.01wt% of the mass of particle A and phosphoric acid accounting for 0.5wt% of the mass of particle A are added; the mixture is ball-milled to control the slurry particle size after ball milling to be 1.2μm, and the slurry is spray-dried to control the inlet air temperature to 220°C, the outlet air temperature to 100°C, and the blast frequency to 80Hz to obtain a spray material with a spray particle size D50=20-40μm; the spray material is placed in a box furnace and sintered in a nitrogen atmosphere at a heating rate of 3°C / min, a sintering temperature of 770°C, a sintering time of 10h, and then cooled naturally to obtain particle C;
[0044] Step S4: Particle B and a carbon source consisting of amino acid titanium and citrate titanium that makes the carbon content in particle D 1.2% are mixed to form a mixture; lithium hydroxide accounting for 0.01wt% of the mass of particle B and iron oxide accounting for 0.01wt% of the mass of particle B are added; the mixture is ball-milled and sand-milled, and the particle size of the slurry after sand milling is controlled to be 0.25μm, and the slurry is spray-dried, and the air inlet temperature is controlled to be 220°C, the air outlet temperature is 100°C, and the blast frequency is 80Hz to obtain a spray material with a spray particle size D50=20-40μm; the spray material is placed in a box furnace and sintered in a nitrogen atmosphere, with a heating rate of 3°C / min, a sintering temperature of 650°C, and a sintering time of 8h, and then cooled naturally to obtain particle D;
[0045] Step S5: Mix particles C and D in a mass ratio of 6:4 for 2 hours and then crush them. During the crushing process, control the air pressure between 0.2-0.4Mpa, the grading frequency is 80-200Hz, and the crushing particle size meets the following requirements: D10>0.30μm, D50=0.7-1.50μm, D90<8μm, D100<15μm. After crushing, mix them again for 2.5 hours to obtain high-density lithium iron phosphate material.
[0046] The SEM spectrum of the lithium iron phosphate positive electrode material prepared according to Example 1 is as follows Figure 2 shown.
[0047] The XRD spectrum of the lithium iron phosphate positive electrode material prepared according to Example 1 is as follows Figure 3 shown.
[0048] Example 2
[0049] This embodiment provides a method for preparing a high-density lithium iron phosphate material, comprising the following steps:
[0050] Step S1: iron oxide is mixed with lithium carbonate and ammonium dihydrogen phosphate in a molar ratio of Li:Fe:P=1.03:1:1.03, and a carbon source mixture consisting of sucrose and polyethylene glycol with a carbon content of 0.05% and titanium dioxide with a doping amount of 1000ppm are added to form a mixture; the mixture is sand-milled to control the sand-milling particle size to 0.80μm to obtain a nano-sized sand-milling slurry; the nano-sized sand-milling slurry is spray-dried to control the air inlet temperature to 220°C, the air outlet temperature to 100°C, and the blast frequency to 80Hz to obtain a spray material with a spray particle size of D50=20-40μm; the spray material is placed in a box furnace and sintered in a nitrogen atmosphere at a heating rate of 3°C / min, a sintering temperature of 780°C, and a sintering time of 10h, and then naturally cooled to obtain a sintered material, which is crushed by a mechanical crusher to control the particle A with D50=6-10μm;
[0051] Step S2: ferrous oxalate, lithium hydroxide and phosphoric acid are mixed in a molar ratio of Li:Fe:P=1.04:1:1.03, and a carbon source mixture consisting of sucrose and polyethylene glycol to make the carbon content in particle B 0.15% and titanium dioxide with a doping amount of 2500ppm are added to form a mixture; the mixture is sand-milled to control the sand-milling particle size to 0.55μm to obtain a nano-sized sand-milling slurry; the nano-sized sand-milling slurry is spray-dried to control the inlet air temperature to 220°C, the outlet air temperature to 100°C, and the blast frequency to 80Hz to obtain a spray material with a spray particle size D50=20-40μm; the spray material is placed in a box furnace and sintered in a nitrogen atmosphere at a heating rate of 3°C / min, a sintering temperature of 500°C, a sintering time of 8h, and then cooled naturally to obtain particles B;
[0052] Step S3: Particle A and a carbon source consisting of sucrose and polyethylene glycol that makes the carbon content of particle C 1.2% are mixed to form a mixture; lithium carbonate accounting for 0.01wt% of the mass of particle A and phosphoric acid accounting for 0.5wt% of the mass of particle A are added; the mixture is ball-milled to control the slurry particle size after ball milling to be 1.2μm, and the slurry is spray-dried to control the inlet air temperature to 220°C, the outlet air temperature to 100°C, and the blast frequency to 80Hz to obtain a spray material with a spray particle size D50=20-40μm; the spray material is placed in a box furnace and sintered in a nitrogen atmosphere at a heating rate of 3°C / min, a sintering temperature of 770°C, a sintering time of 10h, and then cooled naturally to obtain particle C;
[0053] Step S4: Particle B and a carbon source composed of amino acid titanium and titanium oxalate whose content in particle D is 1.2% are mixed to form a mixture; lithium hydroxide accounting for 0.01wt% of the mass of particle B, 0.45wt% of the mass of particle B and 0.02wt% of ferric citrate accounting for the mass of particle B are added; the mixture is ball-milled and sand-milled, and the particle size of the slurry after sand milling is controlled to be 0.25μm, and the slurry is spray-dried, and the air inlet temperature is controlled to be 220°C, the air outlet temperature is 100°C, and the blast frequency is 80Hz to obtain a spray material with a spray particle size D50=20-40μm; the spray material is placed in a box furnace and sintered in a nitrogen atmosphere, with a heating rate of 3°C / min, a sintering temperature of 650°C, and a sintering time of 8h, and then cooled naturally to obtain particle D;
[0054] Step S5: Mix particles C and D in a mass ratio of 6:4 for 2 hours and then crush them. During the crushing process, control the air pressure between 0.2-0.4Mpa, the grading frequency is 80-200Hz, and the crushing particle size meets the following requirements: D10>0.30μm, D50=0.7-1.50μm, D90<8μm, D100<15μm. After crushing, mix them again for 2.5 hours to obtain high-density lithium iron phosphate material.
[0055] Comparative Example 1
[0056] This embodiment provides a method for preparing a high-density lithium iron phosphate material, comprising the following steps:
[0057] Step S1: The iron source and the lithium source are mixed in a molar ratio of Li:Fe:P=1.03:1:1.03, and a carbon source mixture consisting of sucrose and polyethylene glycol with a carbon content of 1.1% and titanium dioxide with a doping amount of 2000ppm are added to form a mixture;
[0058] Step S2: sand-grinding the mixture to control the sand-grinding particle size to 0.80 μm to obtain a nano-sized sand-grinding slurry; spray-drying the nano-sized sand-grinding slurry to control the inlet air temperature to 220° C., the outlet air temperature to 100° C., and the blast frequency to 80 Hz to obtain a spray material with a spray particle size of D50=20-40 μm;
[0059] Step S3: placing the spray material in a box furnace and sintering it in a nitrogen atmosphere, with a heating rate of 3°C / min, a sintering temperature of 770°C, and a sintering time of 10 hours, and then cooling it naturally to obtain a sintered material, and crushing the sintered material by a jet mill, controlling the air pressure to 0.35 MPa and the classification frequency to 140 Hz, to obtain a crushed material with a particle size of D10>0.35 μm, D50=0.7-1.5 μm, D90<10 μm, and D100<30 μm;
[0060] Step S4: The above crushed materials are further subjected to screening, batching, packaging and other processes to obtain the finished lithium iron phosphate product.
[0061] In order to verify the quality of the finished lithium iron phosphate material prepared by the method for preparing high-density lithium iron phosphate material provided by the embodiment of the present invention, the lithium iron phosphate material prepared in the above embodiment 1 and comparative example 1, the conductive agent carbon black and the binder polyvinylidene fluoride are dispersed in N-methylpyrrolidone according to a mass ratio of 90:5:5, and after being evenly dispersed by ball milling, they are coated on aluminum foil and vacuum dried to obtain a positive electrode. The electrolyte is 1 mol / L LiPF6, wherein the solvent volume ratio is EC:DMC:EMC=1:1:1, the diaphragm is Celgard polypropylene film, and the metal lithium sheet is the negative electrode, which are assembled together into a button half-cell. The test voltage range is 2.0V-3.75V, and it is charged to 3.75V in a constant current and constant voltage charging mode, and discharged to 2.0V in a constant current discharge mode. The charge and discharge current is 0.1C per cycle, and the charge and discharge current is 1C per cycle. The test results are shown in Table 1. Among them, the charge and discharge curves (0.1C and 1C) of the button half-cell assembled with the lithium iron phosphate positive electrode material prepared in Example 1 of the present invention are as follows: Figure 4 shown.
[0062] Table 1. Test items and test results of Example 1 and Comparative Example 1
[0063] serial number 0.1C first discharge specific capacity (mAh / g) 1C discharge specific capacity (mAh / g) <![CDATA[Compaction density g / cm 3 > Example 1 158.80 142.60 2.625 Example 2 158.56 142.77 2.628 Comparative Example 1 151.21 130.25 2.410
[0064] According to the above examples and control examples and the test results obtained by testing them, the button half-cell prepared by the high-density lithium iron phosphate material prepared in Example 1 has significantly improved 0.1C initial charge and discharge capacity and 1C discharge capacity compared with Comparative Example 1. In addition, the high-density lithium iron phosphate material prepared in Example 1 uses small particles for filling, and the better particle grading ultimately improves the compaction density of the lithium iron phosphate material.
[0065] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "example", "specific example" or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, unless they are contradictory.
[0066] Although embodiments of the present invention have been shown and described, those skilled in the art will appreciate that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the claims and their equivalents.
Claims
1. A method for preparing a high-density lithium iron phosphate material, characterized in that: The method comprises: Step S1: mixing an iron source with a lithium source and a phosphorus source in a certain ratio, adding a certain amount of a carbon source and additives, ball milling, sand milling, spray drying, and then sintering and crushing at a certain temperature to obtain particles A; Step S2: mixing an iron source with a lithium source and a phosphorus source in a certain ratio, adding a certain amount of a carbon source and additives, ball milling, sand milling, spray drying, and then sintering at a certain temperature to obtain particles B; Step S3: adding a carbon source, a lithium source and a phosphorus source to the particles A, then ball milling, spray drying, and sintering to obtain particles C; Step S4: adding a carbon source, a lithium source, an iron source, and a dopant to the particle B, and then ball milling, sand milling, spray drying, and sintering to obtain particles D; Step S5: uniformly mix the particles C and the particles D in a certain proportion, and then crush and mix them to obtain a high-density lithium iron phosphate material.
2. The method for preparing high-density lithium iron phosphate material according to claim 1, characterized in that: In step S1, the iron source is one or more of ferric phosphate, ferrous oxalate, iron oxide, hydroxyferric phosphate, iron powder, and ferric nitrate; the lithium source is one or more of lithium carbonate, lithium phosphate, lithium hydroxide, lithium dihydrogen phosphate, lithium monohydrogen phosphate, lithium acetate, and lithium nitrate; the phosphorus source is one or more of phosphoric acid, lithium dihydrogen phosphate, ammonium dihydrogen phosphate, diammonium hydrogen phosphate, and ferric phosphate; the lithium source, iron source, and phosphorus source are added in a molar ratio of Li:Fe:P=[1.03-1.04]:1:[1.03-1.04].
3. The method for preparing high-density lithium iron phosphate material according to claim 1, characterized in that: In step S1, the carbon source is one or more of sucrose, glucose, citric acid, starch, and polyethylene glycol; the amount of the carbon source added is based on the carbon content in the particles A being between 0.01% and 0.20%; the additive is one or more of titanium dioxide, ammonium metavanadate, and niobium pentoxide, and the doping amount is controlled between 300 and 3000 ppm.
4. The method for preparing high-density lithium iron phosphate material according to claim 1, characterized in that: In the step S1, the sand grinding particle size is controlled between 0.50-0.90 μm; the sintering temperature is 700-800° C., and the sintering time is 5-15 hours; and the particle size of the particle A is between 3.0-10.0 μm.
5. The method for preparing high-density lithium iron phosphate material according to claim 1, characterized in that: In step S2, the iron source is one or more of ferric phosphate, ferrous oxalate, iron oxide, hydroxyferric phosphate, iron powder, and ferric nitrate; the lithium source is one or more of lithium carbonate, lithium phosphate, lithium hydroxide, lithium dihydrogen phosphate, lithium monohydrogen phosphate, lithium acetate, and lithium nitrate; the phosphorus source is one or more of phosphoric acid, lithium dihydrogen phosphate, ammonium dihydrogen phosphate, diammonium hydrogen phosphate, and ferric phosphate; the lithium source, iron source, and phosphorus source are added in a molar ratio of Li:Fe:P=[1.03-1.04]:1:[1.03-1.04].
6. The method for preparing high-density lithium iron phosphate material according to claim 1, characterized in that: In step S2, the carbon source can be one or more of sucrose, glucose, citric acid, starch, and polyethylene glycol; the amount of the carbon source added is based on the carbon content in the particle B being between 0.05% and 0.30%; the additive is selected from one or more of titanium dioxide, ammonium metavanadate, and niobium pentoxide, and the doping amount is controlled between 300 and 3000 ppm.
7. The method for preparing high-density lithium iron phosphate material according to claim 1, characterized in that: In the step S2, the sand grinding particle size is controlled to be between 0.40-0.80 μm; the sintering temperature is 450-650° C., and the sintering time is 5-15 hours; and the particle size of the particle B is between 2.0-5.0 μm.
8. The method for preparing high-density lithium iron phosphate material according to claim 1, characterized in that: In step S3, the amount of carbon source added is based on the carbon content in the particles C being between 1.1% and 1.4%; the carbon source is one or more of sucrose, glucose, citric acid, starch, and polyethylene glycol; the lithium source is one or more of lithium carbonate, lithium phosphate, and lithium hydroxide; the phosphorus source is one or more of phosphoric acid, ammonium dihydrogen phosphate, diammonium hydrogen phosphate, and lithium dihydrogen phosphate; the ball milling particle size is between 0.80 and 1.50 μm; the sintering temperature is 750-850° C., and the sintering time is 5-10 hours.
9. The method for preparing high-density lithium iron phosphate material according to claim 1, characterized in that: In step S4, the amount of carbon source added is based on the carbon content in the particles D being between 1.2% and 1.6%; the carbon source is one or more of amino acid titanium, titanium oxalate, and titanium citrate; the lithium source is one or more of lithium carbonate, lithium phosphate, and lithium hydroxide; the iron source is one or more of iron oxide, ferrous oxalate, ferric phosphate, and ferric citrate; the dopant is one or more of amino acid titanium, titanium oxalate, and titanium citrate; the sanding particle size is between 0.20 and 0.50 μm; the sintering temperature is 600-750°C, and the sintering time is 5-10 hours.
10. The method for preparing high-density lithium iron phosphate material according to claim 1, characterized in that: In the step S5, the amount of the particles C and the particles D added is in a mass ratio of particles C: particles D = [8:2] - [2:8], and the mixing time is 0.5h-3h; the crushing particle size satisfies: D10>0.30μm, D50=0.7-1.50μm, D90<8μm, D100<15μm, and the crushing is followed by secondary mixing for 0.5-3h to obtain a high-density lithium iron phosphate material.
Citation Information
Cited By
High-compaction and high-capacity lithium iron phosphate material as well as preparation method and application thereof
CN120208182A
Low-temperature-resistant and high-compaction lithium iron phosphate positive electrode material, preparation method thereof and battery
CN121180969A
High-compaction lithium iron phosphate positive electrode material as well as preparation method and application thereof
CN122212072A